If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12(7-3x)+6=100-6(6x)
We move all terms to the left:
12(7-3x)+6-(100-6(6x))=0
We add all the numbers together, and all the variables
12(-3x+7)-(-66x+100)+6=0
We multiply parentheses
-36x-(-66x+100)+84+6=0
We get rid of parentheses
-36x+66x-100+84+6=0
We add all the numbers together, and all the variables
30x-10=0
We move all terms containing x to the left, all other terms to the right
30x=10
x=10/30
x=1/3
| 9r+15=3r-21 | | 15(2z+6)-4=6*(5z)+86 | | 8s-29=s+27 | | 5x-4=24-2x | | 8f+16=f-19 | | 6=(8x²-7x-5) | | =6(8x²-7x-5) | | F(x)=10x-)-x2 | | 3x+20-2x=20 | | 16n−1=7(–2n+17) | | 4x-2=2x+12x= | | 110+5x=4*180 | | x(0.2x-1)=13.2 | | 6x–2=3x+7 | | 3(9g+6)/2=90 | | 8d+2=4d+14 | | 3(x-6)=7.5 | | 45.4=7c-5 | | 264864+35848m=87897667677 | | 7(2x–7)=16x-50 | | 2(3x-4)+5(4x+1)=0 | | 5(7x–4)=21x+50 | | -7+y/4=7 | | 2(4x+8)=5x+45 | | 12+y+10=0 | | 6(x+4)=8x+20 | | 7(a-4)=42 | | 6+y+10=0 | | 4+y+10=0 | | 6.7(2x-3)=35 | | 50=(0,5x+20)+x | | 8e-2=67.6 |